PERMAINAN SEPAK BOLA (DORA) DALAM PEMBELAJARAN PENJASORKES KELAS VI SD NEGERI PALEBON 02 KEC. PEDURUNGAN KOTA SEMARANG TAHUN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study was to find out the yield improvement approaches to learn the game of football with Dora in class VI student Palebon SD Negeri 02 Semarang City Year 2013 . Methods for this research is CLA Class Action research consists of four stages , namely planning ( planning) , action ( action ) , observation ( observation ) danreflection ( reflection ) . Based on the results of research and reference data on indicators of student achievement for the activity to be 75 % , then it can be concluded that the results learn dribbling , passing football approach Dora games ( Sodor ball ) is said to be successful, so the results obtained are consistency indicator of students' learning beyond that is 75%.